2015
DOI: 10.5897/jvmah2014.0358
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on ectoparasite infestation of small ruminants in Sodo Zuria District, Southern Ethiopia

Abstract: A cross-sectional study was conducted to estimate magnitude of small ruminant ectoparasite infestation in Sodo Zuria district from November, 2013 to March, 2014. Out of the total 758 small ruminants, 51.5% sheep and 48.9 % goats were found infected with ectoprasite infestation (p=0.471). Standard identification of 383 ectoprasite specimens demonstrated ticks (34.6%), lice (7.1%), fleas (6.1%) and mange mites (2.8%). Tick and flea infestation were predominant in sheep (p<0.01) whereas mange mite infestations wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
2
5
5
2
Order By: Relevance
“…The occurrence of more infestations in females than in males agrees with the findings of Neog et al (1992), Chakrabarti (1994), Jonsson (2004), Yakhchali and Hossiene (2006), Mbuh et al (2008), Barmon et al (2010); Obi et al (2014) and Yishak et al (2015). Lloyd (1983) reported that higher level of prolactin and progesterone makes females more susceptible to infestation as a result of pregnancy and lactation.…”
Section: = 91 -------------------------------------------------------supporting
confidence: 81%
See 4 more Smart Citations
“…The occurrence of more infestations in females than in males agrees with the findings of Neog et al (1992), Chakrabarti (1994), Jonsson (2004), Yakhchali and Hossiene (2006), Mbuh et al (2008), Barmon et al (2010); Obi et al (2014) and Yishak et al (2015). Lloyd (1983) reported that higher level of prolactin and progesterone makes females more susceptible to infestation as a result of pregnancy and lactation.…”
Section: = 91 -------------------------------------------------------supporting
confidence: 81%
“…This concurs with the findings of Osman (1997), Yakhchali and Hossiene (2006), Onojafe (2008), Mbuh et al (2008), Mulugeta et al (2010), Ohaeri and Ugwu (2013) and Yishak et al (2015) but contrary to Obi et al (2014), who reported fleas to be the dominant ectoparasites in both sheep and goats. Elsaid et al (2013) reported ticks as the most frequent ectoparasites in sheep and fleas as the most ectoparasites in goats.…”
Section: = 91 -------------------------------------------------------contrasting
confidence: 56%
See 3 more Smart Citations